Biochemical Characterization of Different Chemical Components of Parthenium hysterophorus and Their Therapeutic Potential against HIV-1 RT and Microbial Growth. (28th April 2022) - Jaiswal, Jyotsna; Doharey, Pawan Kumar; Singh, Reetika; Tiwari, Priyanka; Singh, Nitika; Kumar, Abhishek; Gupta, Vivek Kumar; Siddiqui, Arif Jamal; Sharma, Bechan
Abstract : Parthenium hysterophorus possesses certain allelochemicals responsible for their medicinal effects. The presence of oils, polyphenols, alkaloids, terpenes, pseudoguaianolides, and histamines in P. hysterophorus has been shown to exhibit medicinal properties. However, the systematic biomedical properties of this plant are still unexplored. The extracts of leaves, stem, and flower of P. hysterophorus, both at low and high temperatures (equivalent to boiling points of different solvents) were prepared. The extracts prepared in hexane, ethylacetate, methanol, and water were analyzed spectrophotometrically and colorimetrically and resolved on TLC for the presence of phytochemicals. The analyses of the free radical quenching potential of plant extracts were done by DPPH assay. The total antioxidant capacity was determined by phosphomolybdate assay and the ferric reducing antioxidant power (FRAP) assay was used to determine the reduction potential of the extracts. The spectrophotometric and qualitative analysis of plant extracts demonstrated the presence of alkaloids, terpenoids, carbohydrates, and cardiac glycosides. The occurrence of more than one Rf values for extracts determined by TLC indicated the presence of more than one phytochemical compound. The P. hysterophorus extracts contained strong antioxidant activity. These extracts exhibited strong antimicrobial activity against Staphylococcus epidermis, Salmonela typhi, Neisseria gonococci or gonococci, Citrobacter, and Shigella flexineri. The evaluation of the antimicrobial potential of P. hysterophorus extracts was done by the disc diffusion method. These extracts also showed significant inhibition against HIV-1 RT activity. The anti-HIV-1 RT activity was done using Roche Kit. The P. hysterophorus extracts displayed the presence of many phytochemicals with strong antioxidant, antimicrobial, and anti-HIV-1 RT properties.